A new frog species of the genus Rugosa from Sado Island, Japan (Anura, Ranidae) - Sekiya, Kunio; Miura, Ikuo; Ogata, Mitsuaki (Zootaxa, 2012)
We describe a new frog species in the genus Rugosa from Sado Island, Japan. This new species, Rugosa susurra, is ge-netically close to R. rugosa Temminck and Schlegel, but is morphologically distinguishable and postzygotically isolatedfrom the latter species. The skin over the entire body is much smoother, and the abdomen and ventral surface of hindlimbare deep yellow whereas these are pale yellow or grayish yellow in R. rugosa. In addition, duration of the advertisementcall of Rugosa susurra is definitely longer than that of R. rugosa. Rugosa susurra is the first endemic amphibian species to Sado Island in Japan.